2022
DOI: 10.1002/jmri.28565
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of the Renal Function, Oxford Classification and Prognostic Risk Stratification of IgAN by Using Intravoxel Incoherent Motion Diffusion‐Weighted Imaging and Blood Oxygenation Level‐Dependent MRI

Abstract: Background Immunoglobulin A nephropathy (IgAN) is the most common primary glomerulonephritis worldwide. Oxford classification including mesangial hypercellularity (M), endothelial hypercellularity (E), segmental sclerosis (S), interstitial fibrosis/tubular atrophy (T), and crescent (C) were recommended to predict the prognosis of IgAN. Purpose To explore whether multiparametric magnetic resonance imaging (MRI) can be applied to assess the renal function, Oxford classification, and risk of progression to end‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The results of this work were consistent with previous studies. 14,16 For example, Liang et al showed that both cortical and medullary D values were significantly lower in patients with IgAN than in healthy volunteers and were significantly lower in patients with lower eGFR. Furthermore, medulla D values decrease successively among control groups and patients with type 2 diabetes with normoalbuminuria and microalbuminuria subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this work were consistent with previous studies. 14,16 For example, Liang et al showed that both cortical and medullary D values were significantly lower in patients with IgAN than in healthy volunteers and were significantly lower in patients with lower eGFR. Furthermore, medulla D values decrease successively among control groups and patients with type 2 diabetes with normoalbuminuria and microalbuminuria subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that considerable variability in ICC values for D* was observed across studies. 14,23,35 Theoretically, the perfusion effect is primarily present at small b-values. To ensure the accuracy and reproducibility of D*, it is imperative to collect more data within the small b-value range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this journal issue, 8 Liang et al investigated whether intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) and BOLD-MRI at 3.0 T MRI can assess renal function and disease prognosis in a prospective cohort of 46 patients with biopsy-proven IgAN. Analysis was performed by two radiologists drawing regions of interest in the renal cortex and medulla, with a high interreader agreement (intraclass correlation coefficient ranging 0.875-0.…”
Section: Expands the Oxford Classification By Including Clinical And ...mentioning
confidence: 99%
“…In this journal issue, 8 Liang et al investigated whether intravoxel incoherent motion diffusion‐weighted imaging (IVIM‐DWI) and BOLD‐MRI at 3.0 T MRI can assess renal function and disease prognosis in a prospective cohort of 46 patients with biopsy‐proven IgAN. Analysis was performed by two radiologists drawing regions of interest in the renal cortex and medulla, with a high inter‐reader agreement (intraclass correlation coefficient ranging 0.875–0.986) of different IVIM‐ and BOLD‐MRI‐derived metrics (true diffusion coefficient [Dt], pseudo‐diffusion coefficient [Dp], perfusion fraction [fp], apparent diffusion coefficient [ADC], and T2* relaxation time, respectively).…”
mentioning
confidence: 99%